2020
DOI: 10.18280/isi.250104
|View full text |Cite
|
Sign up to set email alerts
|

AI Data Driven Approach-Based Endogenous Inputs for Global Solar Radiation Forecasting

Abstract: Controlling the random nature of renewable energy sources such as solar radiation at ground, allows electric grid operators to better integrate it. In this paper, an intelligent datadriven model based on artificial neural network with autoregressive input sequence is developed to forecast the global solar radiation (GSR) time series on a half hour resolution in the site of Agdal, Marrakesh, Morocco. The database that is used to create this model was divided into two subsets. The first subset is used for traini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Jallal et al [33] suggested a Deep Neural Network capable of handling the non-linearity and dynamic behavior of meteorological data and providing accurate real-time predictions of hourly global solar radiation. The neural network used hourly data on global solar radiation and meteorological parameters based on the METEONORM data sets of the city of El Kelaa des Sraghna, Morocco.…”
Section: Deep Neural Network (Dnn)mentioning
confidence: 99%
“…Jallal et al [33] suggested a Deep Neural Network capable of handling the non-linearity and dynamic behavior of meteorological data and providing accurate real-time predictions of hourly global solar radiation. The neural network used hourly data on global solar radiation and meteorological parameters based on the METEONORM data sets of the city of El Kelaa des Sraghna, Morocco.…”
Section: Deep Neural Network (Dnn)mentioning
confidence: 99%
“…In the present work, eight training optimizers (Resilient back Propagation (Rp), One step secant (OSS), Levenberg-Marquardt (LM) Algorithm, Fletcher-Reeves algorithm (Cgf), Polak-Ribiere algorithm (Cgp), Powell-Beale algorithm (Cgb), gradient descent (Gd) algorithm and scaled conjugate gradient algorithm (Scg)) are applied to estimate the ENN model parameters [6,17,18], with the mean square error (MSE) that is used as a loss function. More details about the training process of artificial neural networks are presented in Ref.…”
Section: Elman Artificial Neural Network (Enn) Descriptionmentioning
confidence: 99%
“…The ENN model performance was evaluated using the MSE and the correlation coefficient (R) metrics [19], which are computed by Eq. ( 5) and (6). Subsequently, the influence of the Elman ANN's feedback links order (TDL) on the forecasting accuracy is investigated by changing its value between 1 and 48.…”
Section: Implementation and Analysis Of The Proposed Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning is one of the most important branches of artificial intelligence, which is used in a range of fields and disciplines [2][3][4], including the field of education that we will focus on [5].…”
Section: Introductionmentioning
confidence: 99%